2012
DOI: 10.1097/bpo.0b013e318257640c
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Baby’s Congenital Malformation on the Mother’s Psychological Well-Being

Abstract: These preliminary findings highlight the negative impact that the congenital malformation of clubfoot can have on mothers' psychological well-being and the protective role of social support. Moreover, the positive feedback from the mothers receiving emotional and informational support confirms the importance of implementing intervention protocols in the hospital unit directed to parents of babies with a congenital malformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…A recent study showed that the psycho logical well-being and coping strategies for mothers of children with clubfoot are negatively impacted. 31 This situation might be further exacerbated by difficulties with cast handling and removal. Interestingly, in the study by Pittner and colleagues, 30 there was no difference in parental satisfaction between the 2 casting groups.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the psycho logical well-being and coping strategies for mothers of children with clubfoot are negatively impacted. 31 This situation might be further exacerbated by difficulties with cast handling and removal. Interestingly, in the study by Pittner and colleagues, 30 there was no difference in parental satisfaction between the 2 casting groups.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies in the literature on the experiences of parents of children with clubfoot. 8,13 However, research focusing on the experiences of parents/caregivers of patients with chronic diseases in the clinical setting is increasing. [16][17][18][19] This study assessed emotional distress and parenting stress associated with caring for children with clubfoot using HADS and PSI-SF in which nine (15.5%) parents reported emotional distress and seven (12.0%) had parenting stress.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study conducted among mothers of children with clubfoot reported a negative impact of the diagnosis of clubfoot on their psychological well-being. 13 To this end, we set out to determine the levels of emotional distress and parenting stress among parents of Nigerian children with clubfoot and identify associated risk factors. Furthermore, in Nigeria there is a dearth of research undertaken to assess the experiences of parents of children with clubfoot.…”
Section: Introductionmentioning
confidence: 99%
“…In our center, these patients are referred because of an abnormal US that has already been obtained, and therefore the indications for US are not driven by our clinic. Recent evidence has demonstrated the negative impact a congenital abnormality such as a clubfoot can have on a mother's psychological well-being, as well as the positive feedback of informational and emotional support [15]. Once a family has been given a diagnosis, a discussion of the potential implications of that diagnosis should be done with someone knowledgeable in the subject and should be based on the best available information.…”
Section: Discussionmentioning
confidence: 99%